Osteonecrosis as a complication in pediatric patients with acute lymphoblastic leukemia - Ilaria Riccio; Elvira Pota; Marco Marcarelli; Maria Carmen Affinita; Daniela Di Pinto; Cristiana Indolfi; Nicola Del Regno; Marco Esposito (PAGEPress Publications, 2016)
Osteonecrosis is a significant adverse effect of treatment administered to children suffering from acute lymphoblastic leukemia (ALL) that may have a negative effect on the quality of life. The purpose of this study is to evaluate the rate of secondary vascular osteonecrosis (ON) in a population of pediatric patients with ALL treated with corticosteroids and cytostatic agents. A retrospective analysis of prospectively collected data of the medical records of 328 patients with ALL identified 4 cases with ON, corresponding to 1.2% of all cases observed. Of the 4 patients identified in our study 3 were girls and 1 was a boy, aged from 10 to 16 years old (average age at diagnosis, 12 years). Median time between the diagnosis of ALL and ON was 12.5 months (range, 12 to 36 months). Regarding the lesion size of ON, in all cases the femoral head (monolateral in 1 case and bilateral in 3 cases) was involved and was associated with the scapula-humeral joint in one case. ON of the weight-bearing joints has been identified as a severe complication in children with leukemia that may be associated with the development of articular surface collapse, subsequent debilitating arthritis, sometimes needing arthroplasty. For this reason it is very important to implement prevention strategies, especially in adolescent girls treated with steroids and chemotherapy. An early diagnosis of ON and careful orthopedic follow-up are necessary in order to avoid bone deformations related to the late start or the wrong therapy.